A bilinear structural constitutive model for strain rate-dependent behaviour of human diaphragm tissue. Issue 3 (3rd May 2020) - Gaur, Piyush; Verma, Khyati; Chawla, Anoop; Mukherjee, Sudipto; Jain, Mohit; Mayer, Christian; Chitteti, Ravi Kiran; Ghosh, Pronoy; Malhotra, Rajesh; Lalvani, Sanjeev
Abstract: Diaphragmatic rupture is the tear of the diaphragm muscle result from blunt or penetrating trauma and occurs in about 5% of cases of severe blunt trauma. Both finite element (FE) modelling and experimental testing have enhanced our understanding of the injury mechanisms associated with diaphragmatic rupture. A constitutive model for human diaphragm tissue is developed and implemented via user subroutine ( UMAT ) in LS Dyna that accounts for the strain rate-dependent effects and bilinear behaviour observed experimentally. To better understand the material properties of the human diaphragm, 16 dynamic tensile tests were conducted at three different strain rates of 65/s, 130/s and 190/s from six whole human diaphragms. The engineering stress–strain relationship obtained from these tests showed a bilinear behaviour and strain rate dependency. A strain rate-dependent bilinear stress–strain model was developed, and its parameters were optimised using a genetic algorithm-based inverse characterization method. The results demonstrate a good correlation between experiments and the model, with an average difference of 2 ± 2.8% (mean ± SD) between the optimised FE and experimental load–time curves. The material parameters found in this study can be used in dynamic simulations using FE models of diaphragm tissues.